Managing Project Teams Shortcuts to success - Harrin, Elizabeth (BCS, The Chartered Institute for IT, 2013)
Projects succeed through people, so project managers need to be adept at working with others, especially as projects usually involve a group of people whose day jobs have very little in common. Additionally, project managers tend not to have line management authority but still need to instruct, motivate, coach and cajole the team members. This ebook covers managing the team, the project sponsor and the stakeholders. This is one section of the book "Shortcuts to Success".